Pancreatic ductal adenocarcinoma: Current and evolving therapies - Adamska, A.; Domenichini, A.; Falasca, Marco (MDPI AG, 2017)
Pancreatic ductal adenocarcinoma (PDAC), which constitutes 90% of pancreatic cancers, is the fourth leading cause of cancer-related deaths in the world. Due to the broad heterogeneity of genetic mutations and dense stromal environment, PDAC belongs to one of the most chemoresistant cancers. Most of the available treatments are palliative, with the objective of relieving disease-related symptoms and prolonging survival. Currently, available therapeutic options are surgery, radiation, chemotherapy, immunotherapy, and use of targeted drugs. However, thus far, therapies targeting cancer-associated molecular pathways have not given satisfactory results; this is due in part to the rapid upregulation of compensatory alternative pathways as well as dense desmoplastic reaction. In this review, we summarize currently available therapies and clinical trials, directed towards a plethora of pathways and components dysregulated during PDAC carcinogenesis. Emerging trends towards targeted therapies as the most promising approach will also be discussed.